PERSEPSI BELIA MUSLIM TERHADAP MASAKAN ORANG BUKAN ISLAM DI WILAYAH PERSEKUTUAN KUALA LUMPUR: The Perception of Muslim Youth towards the Cuisine of Non-Muslims in the Federal Territory of Kuala Lumpur - Hasani, Puteri Balqis; Shahrom, Nur Fatin Nabilah Binti (Selangor Humaniora Review, 2023)
Engaging in marketing or business has given a boost to companies' commitment to some production of halal food products. The development of the Malaysian halal industry, which has successfully penetrated the global market, especially in the halal food sector, has advanced Malaysia’s name by making it a respected and organised country. It also makes Malaysia a preferred destination for developing businesses related to halal goods and services. Many misconceptions occur in the definition of halal and illegal products or foods produced by non-Islamic people. The study was conducted to analyse the knowledge of Muslim youth about halal food and the status of halal food provided by non-Islamic people from a fiqh perspective, as well as the knowledge level of Muslim youth on halal food. This survey study uses a mixed quantitative and qualitative approach. The survey involved 253 respondents among Muslim youths in several districts of Kuala Lumpur who answered questionnaires. The data is analysed using SPSS 27 software. The study's results found that the knowledge of concepts showed that most Muslim youths in Kuala Lumpur mastered the concept of halal well. Still, awareness of choosing halal foods was also at a high percentage. Content analysis was conducted through three fiqh books to study non-Islamic cuisine according to the fiqh perspective. According to the study, it is permissible for a Muslim to eat non-Islamic foods, but they should comply with the concept of halal in Islam. Additionally, the results of this study are reinforced by the analysis of the general perception of Muslim youths about non-Islamic foods, which shows that young people are still considering the halal characteristics of foods and premises, even if non-Muslims cook them. This study recommends that young Muslims should choose foods that have a halal logo so as not to cause any future misconduct.